Towards a taxonomy of idea generation techniques - Kai Wang (Foundations of Management, 2019)
Business organizations often need to manage creative work. An important way of promoting creative work is to use idea generation techniques (IGTs). Numerous IGTs have been developed, and choosing from such a big pool of candidates can be demanding, which is further complicated by the elusiveness of the mechanisms of these IGTs. This study aims at developing a taxonomy for IGTs based on their underlying mechanisms of supporting ideation. First, the current literature for the classification of IGTs is reviewed. Then some related creativity theories are consulted and a new classification system is proposed based on these theories and previous studies. Eighty seven IGTs are classified according to the system. The implications for research and practice are discussed.
Keywords: O31; O32; M10; M19; 650; innovation; creativity theories; creativity techniques; idea generation; classification